ESPAÇO E DESIGUALDADES: MAPEAMENTO E ANÁLISE DA DINÂMICA DE EXCLUSÃO/INCLUSÃO SOCIAL NA CIDADE DE PONTA GROSSA (PR) - Nascimento, Ederson do (2008)
This research tried to give a contribution to the knowledge of the relation on the process of unequal socio-spatial structuring in the city of Ponta Grossa, State of Paraná, through the production of a social exclusion/inclusion map. The main purpose was to analyze the life conditions into different places of the urban space by characterizing them starting from the population inhabitant's socioeconomic profile and their home conditions in four important dimensions of the process of social exclusion/inclusion: income autonomy, human development, equity and house quality. The used methodology was summarized into the following stages: rising and revision of the bibliography; construction of a system of social exclusion/inclusion indicators with data, joined by census sections regarding the income and the educational level of family heads, infanto-juvenile education incentive, longevity, presence of women family heads with insufficient education, readiness of basic and sanitary infrastructure, percentile of juridical property of the houses and the existence of improvised homes and slum dwellers areas; and the elaboration of interviews in which aimed to validate and (when it was the case) to update the results shown by the map, as well as the obtaining of qualitative information about the main factors that motivate the occupation of the urban locations for the social classes, and about the life conditions on different areas of the city. The results of the research revealed an urban space characterized by an extreme socioeconomic segregation, fragmented into areas that concentrate populations with different degrees of inclusion or social exclusion. On the first place, it was verified that there is a very close correlation among the positive indicators regarding the population resident's characteristics (especially the levels of income and education) and the indexes of house quality. It was also observed that the space distribution of the social exclusion/inclusion is organized in sections, with the social patterns refusing the central areas – where there is the concentration of populations socially included and they enjoy better life conditions – towards the periphery of the city, places that the exclusion, in relation to the basic elements for a quality of life, is an outstanding characteristic. In short, these aspects evidence the existence of a social inequality in the extent of the process of (re)production of the urban space in Ponta Grossa, as well as, consequently, the hard disparity in relation to the quality of life of the population.